Atlee Pine : Mercy - Book 4 - Baldacci, David (New York, NY : Grand Central Publishing, 2021)
"For her entire life, FBI agent Atlee Pine has been searching for her twin sister, Mercy, who was abducted at the age of six and never seen again. Mercy's disappearance left behind a damaged family that later shattered beyond repair when Atlee's parents inexplicably abandoned her. Now, after a perilous investigation that nearly proved fatal, Atlee has finally discovered not only the reason behind her parents' abandonment and Mercy's kidnapping, but also the most promising breakthrough yet: proof that Mercy survived her abduction and then escaped her captors many years ago. Though Atlee is tantalizingly close to her family at last, the final leg of her long road to Mercy will be the most treacherous yet. Mercy left at least one dead body behind before fleeing her captors years before. Atlee has no idea if her sister is still alive, and if so, how she has been surviving all this time. When the truth is finally revealed, Atlee Pine will face the greatest danger yet, and it may well cost her everything"--
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Officials and employees; Missing persons -- Fiction; Twin sisters -- Fiction; Family secrets -- Fiction; Kidnapping -- Fiction -- Investigation; Virginia -- Fiction; Detective and mystery fiction; Thrillers (Fiction)